Analisis marjin pemasaran Melinjo dl Daerah Istimewa Yogyakarta = Markcting Margin Analisis of Gnetum in Daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRACT: Gnetum is plant which be developed to increase farmer's welfare, but the marketing behaviour is difficult to understand. Based on these reasons, the purpose of the research is to understand and to identify marketing channels, wholesaler role, proportion and establishment of marketing margin. Survey method was used in this research. Sampling was conducted in all regencies of Daerah Istimewa Yogyakarta Province whereas one village of industrial central of gnetum chips, was taken as a sample